ILr1β production is dependent on the activation of purinergic receptors and NLRP3 pathway in human macrophages. Issue 10 (26th June 2015) - Gicquel, Thomas; Robert, Sacha; Loyer, Pascal; Victoni, Tatiana; Bodin, Aude; Ribault, Catherine; Gleonnec, Florence; Couillin, Isabelle; Boichot, Elisabeth; Lagente, Vincent
ABSTRACT: The Nod‐like receptor family protein 3 (NLRP3)‐inflammasome pathway is known to be activated by danger signals such as monosodium urate (MSU). We investigated the role of P2 purinergic receptors in the activation of NLRP3‐inflammasome pathway after MSU treatment of primary human monocyte‐derived macrophages (MDMs). After initial stimulation with a low concentration of LPS (0.1 μg/ml), a 6 h treatment with MSU crystals (250, 500, and 1000 μg/ml) induced the MDMs to release IL‐1β, IL‐1α, and IL‐6 in a dose‐dependent manner. Moreover, the caspase 1 inhibitor Z‐YVAD‐FMK and the cathepsin B inhibitor CA‐074Me reduced production of IL‐1β in a dose‐dependent manner after LPS + MSU treatment We used real‐time reverse transcription‐quantitative PCR to show that treatment with LPS and MSU (500 μg/ml) induced significantly greater expression of NLRP3 and IL‐1β than after treatment with LPS. We also found that MSU treatment induced P2X purinergic receptor 7 (P2X7R) mRNA and protein expression. Furthermore, addition of the P2X7 purinergic receptor antagonist A‐740003 significantly impeded IL‐1β production and pro‐IL‐1β cleavage after treatment with LPS + MSU. Remarkably, RNA silencing of P2X7R (but not P2X4R) inhibited the release of IL‐1β and other M1 macrophage cytokines (such as IL‐1α, IL‐6, and TNF‐α) from MDMs stimulated with LPS + MSU. Taken as a whole, our results show that P2 purinergic receptors and the NLRP3 inflammasome pathway are involved in the secretion of IL‐1β from MSU‐stimulated human macrophages. This pathway may constitute a novel therapeutic target for controlling the inflammatory process in several associated pathologies.—Gicquel, T., Robert, S., Loyer, P., Victoni, T., Bodin, A., Ribault, C., Gleonnec, F., Couillin, I., Boichot, E., Lagente, V. IL‐1β production is dependent on the activation of purinergic receptors and NLRP3 pathway in human macrophages. FASEB J. 29, 4162‐4173 (2015). www.fasebj.org